2017
DOI: 10.1136/bjsports-2016-097095
|View full text |Cite
|
Sign up to set email alerts
|

Functional performance 6 months after ACL reconstruction can predict return to participation in the same preinjury activity level 12 and 24 months after surgery

Abstract: Return to participation in the same preinjury activity level at 12 and 24 months after ACLR was higher in those who passed the criteria compared with those who failed. Individual and combined return-to-activity criteria predicted the outcomes of interest, with the hop tests as consistent predictors at 12 and 24 months after ACLR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
89
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(100 citation statements)
references
References 52 publications
5
89
4
2
Order By: Relevance
“…Several studies have reported that many patients were unable to pass strength, balance, and neuromuscular tests in the time period when many authors allow RTS, typically 6 to 9 months postoperative. 6,16,21,35,43,61,62,81,92,99,103 Boyle et al 16 tested 39 adolescents and 16 adults who underwent transphyseal hamstring ACLR 9 months postoperatively with the functional movement screen and lower quarter Y-Balance tests. An increased risk for lower extremity injury was reported based on an inferior active straight-leg raise score on the functional movement screen.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that many patients were unable to pass strength, balance, and neuromuscular tests in the time period when many authors allow RTS, typically 6 to 9 months postoperative. 6,16,21,35,43,61,62,81,92,99,103 Boyle et al 16 tested 39 adolescents and 16 adults who underwent transphyseal hamstring ACLR 9 months postoperatively with the functional movement screen and lower quarter Y-Balance tests. An increased risk for lower extremity injury was reported based on an inferior active straight-leg raise score on the functional movement screen.…”
Section: Discussionmentioning
confidence: 99%
“…In another report from the same Delaware-Oslo ACL cohort, passing the same RTS criteria accurately predicted return to previous level of play at 1 and 2 years postoperatively with good sensitivity and specificity. 30,52 Of those patients passing the RTS test at 6 months, 81% and 84% returned to the previous level of play at 1 and 2 years postoperatively, respectively, while 44% and 46% of patients who failed at 6 months returned to the previous level at 1 and 2 years postoperatively after passing subsequent RTS testing, respectively. Although the evidence is mounting for objective RTS testing, further research is needed to validate these results and clearly define the best methods of testing.…”
Section: Rts Decision-making Must Include Objective Physical Examinatmentioning
confidence: 99%
“…Passing a test battery including a series of single leg hop and isokinetic tests was associated with lower rerupture rates following RTS, 1 2 and an increased likelihood of returning to previous sporting levels. 3 However, hop and isokinetic tests do not consistently predict successful outcomes following ACL rehabilitation. Losciale et al 4 reported no associations between the use of RTS discharge tests and greater risk of reinjury, stating the low quality of evidence affects our ability to make definitive conclusions.…”
Section: Introductionmentioning
confidence: 99%